2007
DOI: 10.1111/j.1440-1819.2007.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotonergic antidepressant therapy on temperament and character scales in patients with chronic tension‐type headache

Abstract: The purpose of the present study was to assess a group of patients with chronic tension-type headache (CTTH) and control subjects using the personality questionnaire proposed by Cloninger and to determine possible changes in the Temperament and Character Inventory (TCI) patterns of CTTH patients after therapy with serotonergic antidepressants. Forty-five patients with CTTH filled out the TCI and Beck Depression Inventory (BDI) before and after 4-month prophylactic therapy with serotonergic antidepressants. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 67 publications
0
20
2
Order By: Relevance
“…However, some evidence indicates that treatment of affective disorders with tricyclic antidepressants and selective serotonin reuptake inhibitors, drugs that increase the levels of synaptic serotonin, also increases ' self-directedness ' (Black & Sheline, 1997 ;Allgulander et al 1998 ;Agosti & McGrath, 2002 ;Hirano et al 2002 ;Joyce et al 2003 ;Boz et al 2007). One study has even indicated that this increase in ' self-directedness ' has also predictive value for changes in depressive symptoms as measured with BDI (Mazza et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some evidence indicates that treatment of affective disorders with tricyclic antidepressants and selective serotonin reuptake inhibitors, drugs that increase the levels of synaptic serotonin, also increases ' self-directedness ' (Black & Sheline, 1997 ;Allgulander et al 1998 ;Agosti & McGrath, 2002 ;Hirano et al 2002 ;Joyce et al 2003 ;Boz et al 2007). One study has even indicated that this increase in ' self-directedness ' has also predictive value for changes in depressive symptoms as measured with BDI (Mazza et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to HA, ' self-directedness ' has often been correlated with serotonergic markers (Allgulander et al 1998 ;Peirson et al 1999 ;Boz et al 2007). Results from these studies should be seen as circumstantial evidence for the hypothesis and inconsistencies remain, as they do in genetic studies on HA and the serotonin system (Lesch et al 1996 ;Schinka et al 2004 ;Sen et al 2004 ;Munafò et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also tend to be inhibited and shy in social situations (27). People with high HA respond to stressful events with a higher proportion of depressive symptoms and expect a dangerous situation even in the absence of danger (5,25).…”
Section: Discussionmentioning
confidence: 99%
“…The three dimensions of character (selfdirectedness, cooperativeness, and self-transcendence) mature in adulthood and influence personal and social effectiveness by insight learning about self concepts. The TCI has been shown to be sensitive to serotonergic antidepressants in psychiatric and healthy volunteers (Boz et al 2007;Mörtberg et al 2007;Agosti and McGrath 2002;Tse and Bond 2001).…”
Section: Temperamentmentioning
confidence: 99%